A Risk‐Adjusted O–E CUSUM with Monitoring Bands for Monitoring Medical Outcomes. Issue 1 (5th February 2013) - Sun, Rena Jie; Kalbfleisch, John D.
Summary In order to monitor a medical center's survival outcomes using simple plots, we introduce a risk‐adjusted Observed–Expected (O–E) Cumulative SUM (CUSUM) along with monitoring bands as decision criterion.The proposed monitoring bands can be used in place of a more traditional but complicated V‐shaped mask or the simultaneous use of two one‐sided CUSUMs. The resulting plot is designed to simultaneously monitor for failure time outcomes that are "worse than expected" or "better than expected." The slopes of the O–E CUSUM provide direct estimates of the relative risk (as compared to a standard or expected failure rate) for the data being monitored. Appropriate rejection regions are obtained by controlling the false alarm rate (type I error) over a period of given length. Simulation studies are conducted to illustrate the performance of the proposed method. A case study is carried out for 58 liver transplant centers. The use of CUSUM methods for quality improvement is stressed.